Decreased Nucleotide and Expression Diversity and Modified Coexpression Patterns Characterize Domestication in the Common Bean . Issue 5 (21st May 2014) - Bellucci, Elisa; Bitocchi, Elena; Ferrarini, Alberto; Benazzo, Andrea; Biagetti, Eleonora; Klie, Sebastian; Minio, Andrea; Rau, Domenico; Rodriguez, Monica; Panziera, Alex; Venturini, Luca; Attene, Giovanna; et al.
Abstract : About 60% of the nucleotide diversity was lost during domestication of the common bean. The whole pattern of gene expression has also been affected, with changes in the patterns of coexpression among genes and 18% reduction in the overall diversity of gene expression. About 9% of the genes were selected during domestication, which is associated with further reduced diversity of expression. Abstract: Using RNA sequencing technology and de novo transcriptome assembly, we compared representative sets of wild and domesticated accessions of common bean ( Phaseolus vulgaris ) from Mesoamerica. RNA was extracted at the first true-leaf stage, and de novo assembly was used to develop a reference transcriptome; the final data set consists of ∼190, 000 single nucleotide polymorphisms from 27, 243 contigs in expressed genomic regions. A drastic reduction in nucleotide diversity (∼60%) is evident for the domesticated form, compared with the wild form, and almost 50% of the contigs that are polymorphic were brought to fixation by domestication. In parallel, the effects of domestication decreased the diversity of gene expression (18%). While the coexpression networks for the wild and domesticated accessions demonstrate similar seminal network properties, they show distinct community structures that are enriched for different molecular functions. After simulating the demographic dynamics during domestication, we found that 9% of the genes were actively selected during domestication. We also show that selection induced a further reduction in the diversity of gene expression (26%) and was associated with 5-fold enrichment of differentially expressed genes. While there is substantial evidence of positive selection associated with domestication, in a few cases, this selection has increased the nucleotide diversity in the domesticated pool at target loci associated with abiotic stress responses, flowering time, and morphology.